Entre a demonização de Exu e o Dono do marafo curador de Santíssimo (Rio de Janeiro, 1952-1971) - Silva, Larissa Luísa da (2023)
The summary has an excerpt from the years 1952 to 1971 on the demonization of the guardian Exu within the Umbanda religion. Against this movement, we have Exu Seu Sete da Lira with his wonderful curator in the state of Rio de Janeiro, in the Santíssimo neighborhood. The proposal is to analyze the Jornal de Umbanda: Noticioso e Doctrinario da União Espiritista de Umbanda, together with the works presented to the 1st Brazilian Congress of Spiritism of Umbanda, the Umbandist literature of Aluízio Fontenelle and his most famous work: Exu. Thus giving a vast material to think about this demonization. In a methodological analysis of the journal and its Editorial Directors, it is possible to raise questions from the field of power, which are also in direct dialogue with cultural and social history. Now, about the cures made by an Exu, we will have people who seek any kind of cure – be it spiritual or carnal, and who go in search of Umbanda. Be it directly or indirectly. This search will be targeted with the headlines of periodicals of the time about the cures and Exu Seu Sete da Lira himself. According to Alexandre Cumino, thinkers at the first congress denied the importance of exu in umbanda, along with Fontenelle's work that demonized him. But, Renato Ortiz goes beyond this perspective, exu would be everything that Brazilian republican society denied, the black person. Exu carries the black ancestry and resistance of the African matrix within the Umbandist Religion. Exu has black skin and does not wear the white mask of the spirit of Dionysus, however, it is this same mask that is being denied by the current postmodern society. Exu heals. Exu is the way. Exu is life. Exu just IS